Pendidikan Sistem Ganda pada Sekolah Menengah Kejuruan di Sumatera Utara - Abdul Muin Sibuea; I Wayan Dirgayasa (Teknologi dan Kejuruan, 2009)
The purpose of this research is to evaluate the implementation of PSG program in North Sumatera, to know the current and future skills needed by industry/business, to know obstacle factors of PSG implementation, to know efforts done by state-own SMK and industry to improve the PSG program, and pilicies taken to anticipate the future need. The location of the research is Medan City, Tebing Tinggi, Langkat, Deli Serdang, Tapanuli Utara dan Selatan regencies. The population are the state-own vocational schools and industries/business reaching 29 each of them. The data of this research are collected by documentation,ques-tionaire and informal interview. Descriptive-qualitative-quantitative method is used analyzed the data. The research results in (1) Generally the implementation of PSG is an accordance with the purpose of PSG itself eventhough to some extents do not reach its goal yet, (2) Some current and future skills are needed such as new instalation, electrical welding, measurement, accounting, computer application, new design, and English language, (3) Some obstacle factors of implementation of PSG are misperception of PSG by industries, lack of the students, and unbalance of demand and supply, (4) Efforts done are the improvement of facilities, work performanse, proporional fund alocation, and sustainable curriculum revision, and (5) Policies taken by the SMK and industries are well-organized cooperation, new agreement, and sustainable evaluation of the program.